P246 CURBO2–65 Has Better Correlation than CURB65 with Modified Early Warning Scoring System (MEWS). (14th November 2013) - Molugu, C; Falconer, W; Singer, A; Disney, A; Stockton, P; Peers, V; McCulloch, L
Abstract : Introduction: For patients admitted to hospital with pneumonia, CURB65 (confusion, Urea>7, Respiratory Rate>30 and Blood Pressure<90/60) is used to assess severity of the pneumonia (1). MEWS is a score which informs about the physiological status of a patient thus about the patients overall clinical status. One would anticipate CURB65 to be correlated to MEWS however there is no evidence to support correlation particularly on admission. The body's capability to maintain adequate oxygenation when affected by pneumonia is of paramount importance. Oxygen was originally excluded from CURB65 due to non-statistical significance for predicting mortality. We felt CURB65 may not correlate with MEWS on admission hence introduced a new score incorporating oxygen to CURB65 score - CURBO2–65. COPD patient's with SATS <88% or Non-COPD with <94% would score 1 and any patient receiving supplemental oxygen to maintain their SATS in desired range would score 1. The maximum score for oxygenation is 2 and maximum score on CURBO2 65 is 7 instead of 5 as in CURB65. Method: We retrospectively analysed all pneumonia patients (COPD and Non-COPD) admitted to hospital for 2 consecutive months (December 2012 and January2013). Data was collected from our Advancing Quality team who keep a record of all pneumonias admitted. CURB 65 score and MEWS was collected from the documentation on admission and CURBO2 65 was calculated by applying above criteria for oxygenation. Results: Conclusion: CURB65 does not have predictable corelation with MEWS on admission. By incorporating oxygen into CURB65 and converting to CURBO2 65, we demonstrated its enhanced capability to correlate with MEWS on admission.. Further validity prospective studies are required to confirm our findings. Reference: Defining community acquired pneumonia severity on presentation to hospital: an international derivation and validation study W S lim, M M van der Eerden, R Laing, W G Boersma, N Karalus, G I Town, SA lewis, J T Macfarlane